“I am tired of the disease and eating too many medicines”: seeking adolescent’s lived experiences about chronic renal disease - Shah, Rohit; Adsul, Neha (International Journal Of Community Medicine And Public Health, 2020)
Background: Chronic renal disease (CRD), results from a range of conditions that cause irreversible damage to the kidneys and is a recognised major medical problem worldwide. CRD in children and adolescent’s is an enervating condition requiring lifelong treatment in order ‘to survive’. Several researchers have criticised the research on children with CRD as most of these studies rely on standardized tools which seem to be grounded in objectivity and quantification. Methods: In this milieu, this Indian study adopts a qualitative approach underpinned by the philosophy of Husserlian phenomenology with descriptive phenomenology as a method. The primary purpose of the study was to delve into the lives of adolescents suffering from CRDs to understand their perceptions about how this challenging condition affects and changes their lives. Results: CRD is a chronic condition that confines the lives of these adolescents by demanding a major shift to more prescribed and restrictive lifestyle. Conclusions: The lives of the adolescent participants conveyed a paradoxical nature in terms of suffering; struggling to cope with the stringent lifestyle changes and yet trying to be adapting to the disease to moving forward in life.